Electric Differential with Fuzzy logic Controller for direct wheel drive Electric Vehicle - TABTI, Khatir; CHEKROUN, Soufyane (University of Eloued جامعة الوادي, 2022)
This paper presents a new approach applied to driver stability system of an electric vehicle during turns and steering maneuvers. The Direct yaw moment control is generated from the difference between the driving torques of the left and right wheel. Thus, the electric differential must be take account of the speed difference between the two wheels when cornering. To keep vehicle’s stability, the fuzzy logic controller is used to generate the difference on the torques in order to control body slip angle, yaw rate to its desired values. Simulation results in Matlab/Simulink have shown that the pro-posed control scheme takes advantages of electric vehicle and enhances the vehicle stability.
Forum Intervention of Artificial Intelligence and Its Applications. Faculty of Exat science. University of Eloued
Keywords: Electric vehicle, Electric differential, Fuzzy logic control, yaw moment control, Electric motor